MANAGEMENT OF DYSTOCIA DUE TO MACERATED FETUS IN A MARE - SONI, Y; MEHTA, J S; KUMAR, A; TRIPATHI, A; TALLURI, T R (The Indian Journal of Animal Reproduction, 2022)
The present case report puts on record successful management of a mare suffering from dystocia due toinitial stages of maceration of fetus. A full-term pregnant seven-year-old mare was presented with the historyof vaginal discharges followed by mild straining without any progress. The vaginal examination revealed a fullydilated cervix with the presence of a fetus with carpal flexion. The flexion was corrected and fetus was retractedsuccessfully. The mare was administered fluid, analgesic and antibiotic parentally apart from intra-uterine drugtreatment and the mare has resumed normal health.
Keywords: Carpal flexion; Dystocia; Fetus; Maceration; Mare